Relationship Between Free Nutritious Meal Program (MBG) Energy Contribution with Daily Energy Requirements and Nutritional Status Among Students of Wawo Junior High Scholl, Bima District - Rhosmiati; Hairunnisah; Dea Zara Avila; Muammar Iksan (Al-Hijrah Indonesia, 2026)
Background: The Free Nutritious Meal Program is a school-based nutrition intervention designed to support students’ energy intake and nutritional status. Variations in students’ consumption of the provided meals may influence the program’s contribution to daily energy adequacy and nutritional outcomes. Objective: This study aimed to examine the association between the energy contribution of a Free Nutritious Meal Program, daily energy adequacy, and nutritional status among students of SMP Negeri 2 Wawo (Junior High Scholl), Bima Regency. Methods: A cross-sectional study was conducted among 102 students selected through stratified random sampling. Data were collected using two non-consecutive 24-hour dietary recalls and anthropometric measurements. Data were analyzed using descriptive statistics and Pearson correlation tests. Results: The energy contribution of the Free Nutritious Meal Program was significantly associated with daily energy adequacy (p = 0.003). Daily energy adequacy was significantly associated with students’ nutritional status (p < 0.001). In addition, a significant association was found between the program’s energy contribution and nutritional status (p = 0.010). Conclusion: The energy contribution of the Free Nutritious Meal Program was associated with daily energy adequacy and nutritional status among junior high school students. These findings may support the development of school-based nutrition interventions and community nutrition monitoring programs to improve adolescent nutritional health in rural areas.